Liver Abscess: An Update on Current Management - Kumar H.R. (Medical Science: Recent Advances and Applications Vol. 1, 2025)
Liver abscess is a rare condition that causes pain over the right hypochondrium with fever. Liver abscesses are classified into amoebic liver abscesses and pyogenic liver abscesses. Diagnosis is commonly confirmed by performing an ultrasound or computerized tomography. The management of liver abscesses has seen a trend toward minimally invasive procedures like percutaneous drainage and intravenous antibiotics. For abscesses that are larger than 5cm, percutaneous drainage of the abscess is considered the gold standard treatment. Percutaneous drainage can be divided into percutaneous catheter drainage and percutaneous aspiration. Surgical drainage can be divided into open and laparoscopic drainage. In this chapter, the management of liver abscesses was examined, especially the role of percutaneous drainage, includes percutaneous catheter drainage, percutaneous aspiration, and surgical drainage. A comprehensive literature review was conducted using PUBMED, the Cochrane database of systemic reviews, Google Scholar, and Semantic Scholar looking for randomized control trials, non-randomized trials, observational and cohort studies, clinical reviews, systemic reviews, and meta-analyses from 1990 to 2025. Currently, percutaneous drainage of liver abscess is the first-line interventional procedure that is performed for patients with liver abscesses. Open surgical drainage is rarely performed now. The use of percutaneous catheter drainage and antibiotics has led to a 90% success rate. Early diagnosis and prompt initiation of treatment are critical, as they significantly reduce morbidity and mortality.